2018
DOI: 10.1038/s41370-018-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to ambient air pollution and renal function in African Americans: the Jackson Heart Study

Abstract: Renal dysfunction is prevalent in the US among African Americans. Air pollution is associated with renal dysfunction in mostly white American populations, but not among African Americans. We evaluated cross-sectional associations between 1-year and 3-year fine particulate matter (PM 2.5 ) and ozone (O 3 ) concentrations and renal function among 5090 African American participants in the Jackson Heart Study. We used mixed-effect linear regression to estimate associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…We integrated all available evidence to build and characterise a non-linear exposure–response model of the relationship between PM 2.5 and risk of CKD; a flow chart of data curation and description of included studies are available in supplementary figure S1 and table 1 1 2 50–57. For potential inclusion in the meta-regression analyses, we identified six studies on PM 2.5 , one study on secondhand smoke, and three studies on active smoking (online supplementary figure S1 and table 1), leading to a total of 30 data points, 15 of which were from PM 2.5 studies.…”
Section: Resultsmentioning
confidence: 99%
“…We integrated all available evidence to build and characterise a non-linear exposure–response model of the relationship between PM 2.5 and risk of CKD; a flow chart of data curation and description of included studies are available in supplementary figure S1 and table 1 1 2 50–57. For potential inclusion in the meta-regression analyses, we identified six studies on PM 2.5 , one study on secondhand smoke, and three studies on active smoking (online supplementary figure S1 and table 1), leading to a total of 30 data points, 15 of which were from PM 2.5 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, a cohort study based on 669 US male veterans observed that a 2.1 μg/m 3 IQR higher 1-year PM 2.5 was significantly associated with decreased change in eGFR of -1.87 (-2.99, -0.76) mL/min/1.73 m 2 , (12) while another cross-sectional study based on 21,656 Taiwanese concluded an insignificant association (7). To be noted, three other studies have also investigated the similar hypothesis but were not included in the meta-analysis (8,10,11). Two cross-sectional studies in African Americans and Taipei city residents reported insignificant associations (8,11), while another nationwide cohort study among 2,482,737 US veterans found that a 10 μg/m 3 increase in PM 2.5 concentration was associated with significant increased risk of Longitudinal covariates denoted temporal changes in the inconstant variables (i.e., body weight, marriage, drinking, smoking, cooking energy type, and indoor temperature maintenance); the baseline covariates denoted values of the longitudinal variables in the baseline wave and the constant variables (i.e., residence, sex, education, age at 2011, and average BMI).…”
Section: Discussionmentioning
confidence: 99%
“…To be noted, three other studies have also investigated the similar hypothesis but were not included in the meta-analysis (8,10,11). Two cross-sectional studies in African Americans and Taipei city residents reported insignificant associations (8,11), while another nationwide cohort study among 2,482,737 US veterans found that a 10 μg/m 3 increase in PM 2.5 concentration was associated with significant increased risk of Longitudinal covariates denoted temporal changes in the inconstant variables (i.e., body weight, marriage, drinking, smoking, cooking energy type, and indoor temperature maintenance); the baseline covariates denoted values of the longitudinal variables in the baseline wave and the constant variables (i.e., residence, sex, education, age at 2011, and average BMI). Along x-axis, the positive/negative change means increase/decrease in a biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that an increase of 10 µg/m 3 PM 2.5 was associated with a 24% increase in the cardiovascular disease incident and a 76% increase in cardiovascular disease-related death [37]. Other studies that revealed a significant correlation between PM exposure and other human diseases are summarized in Table 1 [38][39][40][41].…”
Section: Air Pollution and Human Diseasesmentioning
confidence: 98%